2022
DOI: 10.3390/diagnostics12020292
|View full text |Cite
|
Sign up to set email alerts
|

Grade 1 and 2 Chondrosarcomas of the Chest Wall: CT Imaging Features and Review of the Literature

Abstract: The purpose of our retrospective article is to review the CT imaging features of chondrosarcomas of the chest wall with pathologic correlation. For 26 subjects with biopsy-proven chondrosarcomas of the chest wall, two musculoskeletal radiologists retrospectively reviewed 26 CT scans in consensus. Descriptive statistics were performed. The mean tumor size was 57 mm. Twenty (20/26, 77%) chondrosarcomas were located in the ribs and six (6/26, 23%) in the sternum. The majority were lytic (19/26, 73%) with <25% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The imaging of the temporomandibular joint and postoperative findings of common foot and ankle surgeries are the topics of two of the included image-rich reviews that discuss common skeletal findings [16,17]. Notably, one article delves into posteromedial lesions of the chest wall, while the other focuses on reviewing grade 1 and 2 chondrosarcomas of the chest wall, providing crucial insights into accurate diagnosis and treatment planning for these complex cases [18,19].…”
Section: Clinical Applications and Reviewsmentioning
confidence: 99%
“…The imaging of the temporomandibular joint and postoperative findings of common foot and ankle surgeries are the topics of two of the included image-rich reviews that discuss common skeletal findings [16,17]. Notably, one article delves into posteromedial lesions of the chest wall, while the other focuses on reviewing grade 1 and 2 chondrosarcomas of the chest wall, providing crucial insights into accurate diagnosis and treatment planning for these complex cases [18,19].…”
Section: Clinical Applications and Reviewsmentioning
confidence: 99%
“…This is because low-grade and high-grade CS share similar radiological features, such as deep endosteal scalloping, calcification, cortical destruction, and soft tissue masses [ 6 ]. Additionally, Del Grande F et al found no statistically significant difference in mean tumor size between grade I CS (56 mm) and grade II CS (57 mm) [ 9 ]. Consequently, a preferred imaging-based modality, such as radiomics, is crucial to develop and provide more reliable preoperative characteristics for differentiating between low-grade and high-grade CS.…”
Section: Introductionmentioning
confidence: 99%